Mawsu'at al Qur'aniyyah al muyassarah - Ibrahim al Abyari (Muasassah Sijil al 'Arab, 1984)
ws.jl.,6-7,10-11.c.1, jl.1-5.c.1-2/stoc6,jl.1=c.1-2; jl.2=1-2; jl.3=c.1-2; jl.4=c.1-2; jl.5=c.1-2; jl.6=c.1; jl.7=c.1; jl.10=c.1; jl.11=c.1